Great session openers, closers, and energisers : quick activities for warming up your audience and ending on a high note - Caroselli, Marlene (McGraw-Hill New YorkUS, 1998)
Describes 100 activities for opening, closing and energizng training and other instructional sessions. Caters for whole class, small group, large group (7+), and pairs or triad formations. Activities include: quizzes; puzzles; conundrums; discussions; getting-to-know-you, and insight/awareness exercises. Provides particulars for each activity including time, class arrangement, group size, needed materials, methodology, follow-up activities, and uninterrupted transitions to the next stage of the session. Includes handouts and transparencies for activities.